Commodity price fluctuations and unemployment in a dependent economy - Jonaki Sengupta; Ranjanendra Narayan Nag; Bhaskar Goswami (Contemporary Economics, 2017)
The interconnected issues of commodity price fluctuation, unemployment and balance of trade developments are of critical importance in times of globalization. The present paper addresses these issues in terms of a monetary dependent economy macro model that applies to a large class of emerging market economies that export their primary products. However, there exists a manufacturing sector that produces non-traded goods using imported capital goods as an input. Moreover, in such an emerging economy, the stocks of primary commodities constitute a widely used financial asset, among other assets. Thus, the price of these primary commodities behaves as an asset price, which has significant implications for the nature of the interlinkage between the real sector and the financial sector of the economy. In an absence of any capital account transactions, and under a fixed exchange rate regime, the paper examines the effects of supply shock, devaluation, capital flow and fiscal policy on major macro variables, including terms of trade, the stock of primary commodities and real money balances. The result points to the contractionary implications of devaluation, while an exogenous increase in food production produces favorable macroeconomic outcomes.
Keywords: E6; F41; F62; 330; Commodity price fluctuation; unemployment; emerging market Economies; globalization; dependent economy